1973
DOI: 10.1002/star.19730250904
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Starch Granule Size and Distribution in 29 Barley Varieties

Abstract: The starch granule size and distribution has been determined on 29 different samples of barley. There is a wide range in the ratio of small to large granules which varies from a minimum of 5.5:1 to a maximum of 37:1. Small granules were separated from large granules in four varieties and the average weight of the granules determined. From these values the actual percentage of small granules in the original barley starch was determined. Small granule starch may account for from 6.2–30.6% of total starch weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 3 publications
1
13
1
1
Order By: Relevance
“…The large lenticular granules (type A) are 25-40 μm long, are lower in number but represent up to 85-90 % of the total weight of starch. The small (type B), spherical granules are < 10 μm in diameter, representing about 70-95 % of the total number of granules, but only 10-15 % of the total starch weight (Goering et al, 1973b). (See Plate IV in the colour section between pages 230 and 231).…”
Section: Structure Of the Cultivated Barley Kernelmentioning
confidence: 99%
“…The large lenticular granules (type A) are 25-40 μm long, are lower in number but represent up to 85-90 % of the total weight of starch. The small (type B), spherical granules are < 10 μm in diameter, representing about 70-95 % of the total number of granules, but only 10-15 % of the total starch weight (Goering et al, 1973b). (See Plate IV in the colour section between pages 230 and 231).…”
Section: Structure Of the Cultivated Barley Kernelmentioning
confidence: 99%
“…The proportions of individual size fractions of starch granules are likely to be influenced by varietal factors. This has been confirmed by a number of authors 2,6,9,15,18 . At the observed variety set, the influence of varieties on the total variability of the ratio of small and large Results obtained by the means of the GFFF method confirmed the highly significant effect of variety (84%).…”
Section: )79087 %2( (-7'977-32mentioning
confidence: 62%
“…Raeker et al (1998) who tested the size distribution of starch granules by the method LALLS in 34 samples of 12 wheat varieties cultivated in eastern part of the USA recorded marked variety differences. Important variety differences in size of starch granules were also recorded with malting barley, even compared with the results from the sites of very different agro-ecological conditions (Goering et al 1973). Psota et al (2000) found statistically significant differences among small and great starch granules between spring barley varieties Novum and Kompakt.…”
Section: Resultsmentioning
confidence: 81%